Cross‐sectional comparison of health‐span phenotypes in young versus geriatric marmosets. Issue 2 (21st January 2019) - Ross, Corinna N.; Adams, Jessica; Gonzalez, Olga; Dick, Edward; Giavedoni, Luis; Hodara, Vida L.; Phillips, Kimberley; Rigodanzo, Anna D; Kasinath, Balakuntalam; Tardif, Suzette D.
Abstract : The development of the marmoset as a translational model for healthspan and lifespan studies relies on the characterization of health parameters in young and geriatric marmosets. This cross‐sectional study examined health phenotypes in marmosets for five domains of interest for human health and aging: mobility, cognition, metabolism, homeostasis, and immune function. Geriatric marmosets were found to have significant executive function impairment when compared to young animals. While geriatric animals did not show gross abnormalities in mobility and measures of locomotion, their types of movement were altered from young animals. Geriatric marmosets had alterations in cardiac function, with significantly increased mean arterial pressures; metabolism, with significantly lower VO2 ; and suppressed immune function. Further, this study sought to characterize and describe histopathology for both young and geriatric healthy marmosets. Overall this study provides a characterization of health parameters for young and geriatric marmosets which will greatly enhance future aging and interventional testing in marmosets. Abstract : This research provides a cross‐sectional examination of parameters of health in young and geriatric marmosets. Geriatric marmosets are found to have significant impairments of health for each of the five domains examined: mobility, cognition, metabolism, homeostasis, and immune function. As a non‐human primate model, marmosets offer many advantages for the study of aging and healthspan.